An Analysis of Figurative Language in Maroon 5 – Nobody’s Love Song Lyrics - Farhan Muhammad; Didin Nuruddin Hidayat; Alek Alek (Wanastra: Jurnal Bahasa dan Sastra, 2021)
Beautiful words have special meanings and involve expressing ideas in song lyrics through figurative language. This study discussed an analysis of the figurative language in the Maroon 5 song’s lyrics. This study emphasizes the use of figurative language and meaning in the lyrics of the song "Nobody's Love" by Maroon 5. Furthermore, the data source was taken from the lyrics of the Maroon 5 song lyrics. This research employed the descriptive qualitative model. In the analysis, the procedure began by reading the lyrics. Second, the researchers sought to identify words, phrases, and phrases that involved figurative language and catch each figurative language's context. Thirdly, the researchers took some notes about figurative language. Finally, the researchers classified and re-checked the details and analyzed them. The next step was the discussion of each category's results. The last step was drawing conclusions based on the report. The data showed five types of figurative language found in the lyrics of this song: Personification 20%, Hyperbole 30%, Irony 20%, Simile 20%, and Repetition 20%.